Akar Teosofis Filsafat Perennial dan Implikasinya pada Pendidikan Islam - Muhammad Rusydi (EKSPOSE, 2017)
Perennial philosophy has a real implication towards philosophical frame of Islamic education. This implication influences the Islamic education to strengthen the transcendental values that are immanent to the creature of human as khalifatullah fil ardhi. It implies that the implication of perennial philosophy towards philosophical frame of Islamic education must be able to provide wisdom among humans to understand their existence as a creature that relates closely to The Sacred and The One.